Maine’s Libraries Weather the War on Books - Sampson, Michelle R. (Maine Policy Review, 2024)
Public and school libraries provide many things to their communities. They hold programs and events, provide services and meeting spaces, and in the case of public libraries, often serve as community centers. Perhaps most importantly, libraries level the playing field by providing free and unencumbered access to resources and information, regardless of one’s age, financial status, ability, level of education, or other characteristics. Within the last few years, however, the country has seen an enormous rise in attempts to hinder that access. Maine is by no means a battleground state in the war on books, but the state has not escaped attempts to censor. This article recaps recent challenges to books in Maine public and school libraries and places these actions within the greater context of challenges nationwide.